Blinatumomab compared with standard of care for the treatment of adult patients with relapsed/refractory Philadelphia chromosome–positive B‐precursor acute lymphoblastic leukemia. Issue 2 (18th October 2019) - Rambaldi, Alessandro; Ribera, Josep‐Maria; Kantarjian, Hagop M.; Dombret, Hervé; Ottmann, Oliver G.; Stein, Anthony S.; Tuglus, Catherine A.; Zhao, Xiaoyue; Kim, Christopher; Martinelli, Giovanni
Abstract : Background: A single‐arm, phase 2 trial demonstrated the efficacy and safety of blinatumomab, a bispecific T‐cell–engaging antibody construct, in patients with relapsed/refractory (r/r) Philadelphia chromosome–positive (Ph+) acute lymphoblastic leukemia (ALL), a rare hematologic malignancy with limited treatment options. This study compared outcomes with blinatumomab with those of a historical control treated with the standard of care (SOC). Methods: The blinatumomab trial enrolled adult patients with Ph+ ALL who were r/r to at least 1 second‐generation tyrosine kinase inhibitor (n = 45). Propensity score analysis (PSA) was used to compare outcomes with blinatumomab with those of an external cohort of similar patients receiving SOC chemotherapy (n = 55). The PSA mitigated confounding variables between studies by adjusting for imbalances in the age at diagnosis and start of treatment, sex, duration from diagnosis to most recent treatment, prior allogeneic hematopoietic stem cell transplantation, prior salvage therapy, and number of salvage therapies. Bayesian data augmentation was applied to improve power to 80% with data from a phase 3 blinatumomab study in r/r Philadelphia chromosome–negative ALL. Results: In the PSA, the rate of complete remission or complete remission with partial hematologic recovery was 36% for blinatumomab and 25% for SOC, and this resulted in an odds ratio of 1.54 (95% confidence interval [CI], 0.61‐3.89) or 1.70 (95% credible interval [CrI], 0.94‐2.94) with Bayesian data augmentation. Overall survival favored blinatumomab over SOC, with a hazard ratio of 0.81 (95% CI, 0.57‐1.14) or 0.77 (95% CrI, 0.61‐0.96) with Bayesian data augmentation. Conclusions: These results further support blinatumomab as a treatment option for patients with r/r Ph+ ALL. Abstract : A single‐arm, phase 2 trial has demonstrated the efficacy and safety of blinatumomab, a bispecific T‐cell–engaging antibody construct, in patients with relapsed/refractory (r/r) Philadelphia chromosome–positive (Ph+) acute lymphoblastic leukemia (ALL), a rare hematologic malignancy with limited treatment options. Using propensity score analysis, this study demonstrates that efficacy outcomes (complete remission and overall survival) from the phase 2 trial with blinatumomab compare favorably with those for a cohort of similar patients with r/r Ph+ ALL treated with standard‐of‐care chemotherapy.